Investment Analysis of ITMG and PTBA Stocks in 2024 Using the Modern Portfolio Theory Approach - Rasdanu Rasdanu; Rachmad Arif Hidayat; Nicko Albart (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the investment efficiency of ITMG and PTBA shares during 2024 using the Modern Portfolio Theory (MPT) approach. The Efficient Frontier and Capital Allocation Line (CAL) methods are applied to identify optimal portfolio combinations that maximize returns and minimize risk. Secondary data, in the form of daily closing prices of shares, were collected from the Indonesia Stock Exchange and Investing.com. The results of the analysis show that ITMG shares have a higher average daily return than PTBA, but with lower volatility. The low correlation between the two stocks creates effective diversification opportunities. Portfolio simulations form an Efficient Frontier that depicts various combinations of returns and risks, while the Capital Allocation Line shows the linear relationship between risk-free rates and optimal portfolios. The optimal portfolio achieves a combination of a 0.03% return with a risk of 1.91%, while the use of leverage can increase the expected return to 0.04% with a risk of 3.82%. This research emphasizes the importance of managing a combination of assets in one sector to improve investment efficiency. These findings are expected to serve as a strategic guide for investors in optimizing their portfolios of coal mining sector stocks amid the dynamics of the Indonesian capital market.